Men to Villains: Competitive Masculinity in The Lighthouse. Issue 3 (23rd March 2023) - Coleman, Madison
This paper investigates the competitive nature of masculinity as presented in Robert Egger's film The Lighthouse . Applying gender theory, I examine three crucial scenes in the film that demonstrate the two protagonists' pursuit of ascendance, which manifests as their lust to possess the lamp of the lighthouse. Borrowing from the works of sociologists, anthropologists, and historians, I was able to understand the naturally recurring crises of masculinity that circulate around a hegemonic model of the masculine ideal, ultimately leading to competition between men to achieve said hegemony. The Lighthouse proves this enduring phenomenon through Robert Pattinson and Willem Dafoe's volatile relationship and their brutal demise. While the film might not propose a direct solution, I argue it serves as a bleak reminder of how misogyny and toxic masculinity harm men and their relationships with one another.